2011
DOI: 10.1186/1743-422x-8-72
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Nucleos(t)ide Analogues Therapy for Adults With Chronic Hepatitis B reduces the Risk of Long-Term Complications: a meta-analysis

Abstract: BackgroundThe effect of antiviral therapy in chronic hepatitis B (CHB) on reducing the risk of long-term complications (LTCs) remains unclear so far. To study whether long-term nucleos(t)ide analogues therapy can reduce the risk of long-term complications.MethodsWe searched MEDLINE, EMBASE, OVID, the Cochrane Central Register of Controlled Trials. Relative risks (RRs) of long-term complications with or without treatment were studied. Also subgroup analyses including the status of drug-resistance, HBeAg and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 37 publications
2
49
0
Order By: Relevance
“…These data strongly suggested that ETV monotherapy and combinations of NUCs are superior to LAM, ADV, or LDT monotherapy. A greater effect was observed in patients who achieved sustained virological response, while the benefit in nonresponders is unclear (Zhang et al, 2011;Papatheodoridis et al, 2010;Ohishi and Chayama, 2012). In our study, we found that antiviral treatment by both monotherapy and combinations of NUC significantly improved liver function.…”
Section: Et Al 2269supporting
confidence: 57%
See 2 more Smart Citations
“…These data strongly suggested that ETV monotherapy and combinations of NUCs are superior to LAM, ADV, or LDT monotherapy. A greater effect was observed in patients who achieved sustained virological response, while the benefit in nonresponders is unclear (Zhang et al, 2011;Papatheodoridis et al, 2010;Ohishi and Chayama, 2012). In our study, we found that antiviral treatment by both monotherapy and combinations of NUC significantly improved liver function.…”
Section: Et Al 2269supporting
confidence: 57%
“…In patients already infected with HBV, antiviral therapy remains the best strategy to prevent liver cirrhosis and HCC (Lim et al, 2009;Chan et al, 2012;Kwon and Lok, 2011;Kim et al, 2011). Major progress in the treatment of chronic hepatitis B has recently been made during the last decade with the development of antiviral drugs, especially nucleos(t)ide analogs (NUCs) (Fung et al, 2011;Liaw et al, 2011;Zhang et al, 2011). Some data supporting the benefit of antiviral therapy on the prevention of HCC in chronic hepatitis B patients has been shown in a few randomized controlled trials (Zhang et al, 2011;Jin et al, 2011;Lim et al, 2011;Tujios and Lee, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that ETV has low incidence of HCC but these studies did not have a control arm 9. A meta‐analysis and a systematic review showed that NAs can reduce liver complications, including HCC 26, 27. Other studies have begun to show that control of sustained viral loads through drugs such as NAs is important in preventing long‐term complications.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term viral suppression was found to be associated with histologic improvement in the reduction of fibrosis and ultimately regression of cirrhosis [13]. Furthermore, a study has demonstrated that adult patients with CHB need over 2 years of NUC treatment to reduce risk of cirrhosis, HCC or CHB-related death [14]. In order to achieve and maintain virologic suppression, avoid virologic breakthrough, and attain undetectable levels of HBV DNA, optimal medication adherence is essential [15].…”
Section: Introductionmentioning
confidence: 99%